Effect of Photodynamic Therapy on Aggressive Periodontitis - A Systematic Review - Reddy.V, Dr.Prathyusha; Reddy.V, Dr.Chandrasekhara; R.V.S, Dr.Krishna Kumar; K.M, Dr.Sudhir; G, Dr.srinivasulu (International Journal of Scientific Research and Management (IJSRM), 2017)
To analyze the available scientific evidence on the effects of photodynamic therapy with scalingand root planning on aggressive periodontitis. A broad literature search was performed using bothelectronic database and hand search. The databases like MEDLINE, COCHRANECENTRAL, GOOGLESCHOLARS, EBSCO and PROQUEST were used for online search. Hand search was performed in theinstitute library, articles that satisfied the inclusion criteria comparing effectiveness of photodynamictherapy on aggressive periodontitis were selected. Included studies were subjected to critical analysisfollowing the Cochrane Collaboration tool for evaluating the risk of bias. The initial search resulted in 112articles; our final review included 8 articles. Out of 8 studies 6 studies showed photodynamic therapy as anadjunct to scaling and root planning was effective than scaling and root planning. 1 study showedantibiotics with scaling and root planning was effective than photodynamic therapy.1 study did not showany significant changes after photodynamic therapy. With the constraints of limited available literaturephotodynamic therapy is effective with scaling and root planning for the management of aggressiveperiodontitis. But, the antibiotics with scaling and root planning show a greater impact on the clinicaloutcomes of aggressive periodontitis